Devices for Measuring Cervical Dilation During Labor: Systematic Review and Meta-analysis. Issue 4 (April 2018) - Brancadoro, Margherita; Tognarelli, Selene; Fambrini, Franco; Ragusa, Antonio; Menciassi, Arianna
Abstract : Importance: Measurement of cervical dilation is one of the major indicators of labor progression. At present, the criterion standard for this evaluation is digital examination, which results are sometimes inaccurate and extremely dependent on the subject (ie, obstetrician or midwife) experience. Objective: In this systematic and meta-analysis review, the authors have gathered the vast majority of the instruments used for measuring cervical dilation and their clinical application; main features, potentialities, and the most significant constraints are underlined for each device. Evidence Acquisition: Three of the most popular databases (ie, Web of Science, PubMed, and ClinicalTrials.gov) were used to identify all available cervimeters, by using single or combinations of the following keywords: "cervical, " "dilation or dilatation, " "cervimetry, " "cervix, " "uterine, " "measurement, " "labour or labor, " "birth, " and "monitoring." Only articles describing the design or a specific clinical application of an instrument for cervical dilation measurement during labor were selected. Results: Twenty-five articles were deeply investigated by classifying them in 4 different homogenous groups on the basis of the method proposed for measuring cervical dilation. Suitable devices have not been realized yet, and this is the reason why nowadays the gynecologist/obstetrician still evaluates labor progression by digital examination. Conclusions and Relevance: Based on a critical analysis of the selected devices, ultrasound seems to be the most promising technology for future cervimetry realization; ultrasound is accurate in distance measurement, and the behind technology can be miniaturized. However, additional studies are necessary for optimizing the technology and developing an optimal solution. Target Audience: Obstetricians and gynecologists, family physicians. Learning Objectives: After completing this activity, the learner should be better able to critique the effectiveness of digital examination, evaluate the instruments used for measuring cervical dilation and their clinical application, and choose the best solution for future cervimetry.